1989
DOI: 10.1001/archotol.1989.01860270043012
|View full text |Cite
|
Sign up to set email alerts
|

The Transfacial Approach for Combined Anterior Craniofacial Tumor Ablation

Abstract: \s=b\The transfacial approach to the anterior cranial fossa for tumor removal provides for excellent surgical exposure, improved postoperative appearance, and a minimum of complications. The technique is different from previously reported combined craniofacial ablative procedures in that the head and neck surgeon and the neurosurgeon approach the anterior fossa mass through the same facial incision, thus avoiding the need for a separate craniotomy incision. The formation of a vascularized nasofrontal bone flap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Several articles on patients who underwent craniofacial resection reported results as good as ours, but the results could not be included in the metaanalysis either because of large numbers of tumors with noncarcinoma histologies or because of a short followup. 8,9,46,[197][198][199] Nevertheless, several reports related outcomes better than ours for patients with squamous cell carcinoma, 48,56,106,100,110,117,132,137,147,160,168,176 for patients with glandular carcinoma, 160,168,184 and for patients with adenocarcinoma. 136,146 The systematic review revealed a steady improvement in treatment results for patients with squamous cell carcinoma and glandular carcinoma (Fig.…”
Section: Histologymentioning
confidence: 75%
“…Several articles on patients who underwent craniofacial resection reported results as good as ours, but the results could not be included in the metaanalysis either because of large numbers of tumors with noncarcinoma histologies or because of a short followup. 8,9,46,[197][198][199] Nevertheless, several reports related outcomes better than ours for patients with squamous cell carcinoma, 48,56,106,100,110,117,132,137,147,160,168,176 for patients with glandular carcinoma, 160,168,184 and for patients with adenocarcinoma. 136,146 The systematic review revealed a steady improvement in treatment results for patients with squamous cell carcinoma and glandular carcinoma (Fig.…”
Section: Histologymentioning
confidence: 75%
“…Single frontal burr hole [29,30] Bifrontal craniotomy with multiple burr holes [16] Parasagittal burr holes and Midas Rex saw [53] Anterior subcranial approach [24,63] Facial disassembly approach [25,27] Frontal sinusotomy approach [64] Nasofrontal swing approach [23] [18,19] and Dias et al [51], operative mortality has been consistently reported to be under 5% (Tables VI, VII) [13,14,24,42,48,49]. A total of 37 postoperative deaths were identified in this review, and meningitis was the most common cause (Table VIII).…”
Section: Table II Technical Variations Of Craniotomymentioning
confidence: 99%
“…Today, skull base surgery teams depend on head and neck surgeons, neurosurgeons, microvascular plastic surgeons, maxillofacial prosthodontists, interventional and neuroradiologists, radiation oncologists, neuroanesthesiologists, intensivists, and rehabilitation specialists to successfully remove skull base malignancies and then reconstruct and rehabilitate patients. These cooperative efforts have improved survival, morbidity, and mortality of skull base surgery [12][13][14][15][16][17][18][19][20][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Operative microscope can be used if necessary. Tumor extension into the anterior cranial fossa can be removed as described by Panje et al [2] by additional incisions along the eyebrows from the glabellar incision and elevation of nasofrontal fl ap as in osteoplastic frontal sinus surgery and drilling the posterior frontal sinus. After en bloc tumor resection of tumor, the nasal fl ap is repositioned in its original postion.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Dandy [2] introduced craniofacial surgery in 1941 for orbital tumors. It was popularized by Ketcham et al [10] who made it an accepted option for nasal sinus apex tumors.…”
Section: Review Of Literaturementioning
confidence: 99%